Fully Automatic Assessment of Speech of Children with Cleft Lip and Palate - Maier, A.; Nöth, E.; Batliner, A.; Nkenke, E.; Schuster, M. (Informatica)
Fully Automatic Assessment of Speech of Children with Cleft Lip and Palate